2016
DOI: 10.1186/s13002-016-0109-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting indigenous knowledge of subsistence farmers’ for the management and conservation of Enset (Ensete ventricosum (Welw.) Cheesman) (musaceae family) diversity on-farm

Abstract: BackgroundEnset (Ensete ventricosum (Welw.) Cheesman) belongs to the order sctaminae, the family musaceae. The Musaceae family is subdivided into the genera Musa and Ensete. Enset is an important staple crop for about 20 million people in the country. Recent publications on enset ethnobotany are insignificant when compared to the diverse ethnolingustic communities in the country. Hence, this paper try to identify and document wealth of indigenous knowledge associated with the distribution, diversity, and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 23 publications
(52 reference statements)
7
62
0
Order By: Relevance
“…The relative importance of non-elite cultivars is in support of the hypothesis that farmers in Togo are still doing subsistence farming by maintaining and propagating existing diversity. Similar results were reported by Yemataw et al (2016) in Ethiopia and Zietz and Seals (2006) in Mexico. This study also revealed, like it was the case in Benin (Agre et al, 2015) an unequal distribution of cultivars throughout surveyed sites.…”
Section: Discussionsupporting
confidence: 79%
“…The relative importance of non-elite cultivars is in support of the hypothesis that farmers in Togo are still doing subsistence farming by maintaining and propagating existing diversity. Similar results were reported by Yemataw et al (2016) in Ethiopia and Zietz and Seals (2006) in Mexico. This study also revealed, like it was the case in Benin (Agre et al, 2015) an unequal distribution of cultivars throughout surveyed sites.…”
Section: Discussionsupporting
confidence: 79%
“…In East and Central Africa, it is a significant dietary component, ranging from about 20% of daily total food intake in Uganda up to 80% in parts of Rwanda (Abele et al, 2007). Also, the East African highland cooking bananas “Matooke” (triploid A genome East Africa group; AAA-EA) are culturally important in East Africa, with a diverse range of varieties and specific uses (Karamura et al, 1999, 2004; Kalyebara et al, 2007). In West Africa, plantains (AAB group) are grown in mixed cropping systems and play a similar role for food security and income.…”
Section: Introductionmentioning
confidence: 99%
“…Productivity can be enhanced in multiple ways: increasing the spacing between Enset plants (Shumbulo et al 2012), choosing the proper type of corm according to the level of soil fertility and agroecology (Birmeta 2004), undertaking biotechnological studies to discover new varieties that can adapt to the cool climatic conditions, controlling diseases (Yemataw et al 2016), and using technologies to improve the production process of kocho (Ayele and Sahu 2014).…”
Section: Mapping the Supply And Demand Of Kochomentioning
confidence: 99%